A Physician's Guide for Workers' Return to Work During COVID-19 Pandemic. Issue 3 (March 2021) - Baptista, Marcos C.; Burton, Wayne N.; Pawlecki, Brent; Pransky, Glenn
Abstract : Objective: Higher probability of developing severe COVID-19 has been associated with health risk factors and medical conditions which are common among workers globally. For at risk workers, return to work may require additional protective policies and procedures. Methods: A review of the medical literature was conducted on health risk factors and medical conditions associated with increased COVID-19 morbidity and mortality, standardized measures for community COVID transmission, and occupation-specific risk. Results: The relative risk of acquiring and the severity of COVID-19 for workers is associated with three pillars: individual risk, workplace risk, and community risk. Matrices were developed to determine a worker's individual risk based on these three pillars. Conclusions: A practical decision tool is proposed for physicians evaluating and managing individual worker COVID-19 risk in the context of returning to work.